Strategies of Power, Tactics of Emancipation. Hidden Curriculum and Practical Consciousness in the Education of Teachers - Włodarczyk, Rafał (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2020)
The aim of this paper is to present the questions associated with hidden curriculum in the perspective of cultural and political anthropology. Focusing on division and distribution of disciplinary power and authority in the space of school, it explores the role of a teacher in the process of empowerment of pupils and regaining by them the subject position. The article develops studies undertaken in the book "Lévinas. W stronę pedagogiki azylu" ("Lévinas. Toward the Pedagogy of Asylum").
Keywords: authority; critical pedagogy; definition of the situation; discursive consciousness; division and distribution of disciplinary power; education of teacher; emancipation; empowerment; hidden curriculum; ontological security; practical consciousness; reflexivity; routine